Nicotine but not saline self-administering or yoked control conditions produces sustained neuroadaptations in the accumbens shell - Domi, Ana; Lucente, Erika; Cadeddu, Davide; Adermark, Louise (Frontiers in Molecular Neuroscience, 2023)
Using yoked animals as the control when monitoring operant drug-self-administration is considered the golden standard. However, instrumental learning per se recruits several neurocircuits that may produce distinct or overlapping neuroadaptations with drugs of abuse. The aim of this project was to assess if contingent responding for nicotine or saline in the presence of a light stimulus as a conditioned reinforcer is associated with sustained neurophysiological adaptations in the nucleus accumbens shell (nAcS), a brain region repeatedly associated with reward related behaviors. To this end, nicotine- or saline-administrating rats and yoked-saline stimulus-unpaired training conditions were assessed in operant boxes over four consecutive weeks. After four additional weeks of home cage forced abstinence and subsequent cue reinforced responding under extinction conditions, ex vivo electrophysiology was performed in the nAcS medium spiny neurons (MSNs). Whole cell recordings conducted in voltage and current-clamp mode showed that excitatory synapses in the nAcS were altered after prolonged forced abstinence from nicotine self-administration. We observed an increase in sEPSC amplitude in animals with a history of contingent nicotine SA potentially indicating higher excitability of accumbal MSNs, which was further supported by current clamp recordings. Interestingly no sustained neuroadaptations were elicited in saline exposed rats from nicotine associated visual cues compared to the yoked controls. The data presented here indicate that nicotine self-administration produces sustained neuroadaptations in the nAcS while operant responding driven by nicotine visual stimuli has no long-term effects on MSNs in nAcS.